Insider-resistent Distributed Storage Systems - Eikel, Martina

Preference Learning - Fürnkranz, J.; Hüllermeier, Eyke (Encyclopedia of Machine Learning and Data Mining)

Proceedings 26. Workshop Computational Intelligence KIT Scientific Publishing, Karlsruhe, Germany

Extreme F-measure maximization using sparse probability estimates - Jasinska, K.; Dembczynski, K.; Busa-Fekete, Robert; Klerx, Timo; Hüllermeier, Eyke (Proceedings ICML-2016, 33th International Conference on Machine Learning, New York, USA)

Learning to aggregate using uninorms, in Proceedings ECML/PKDD-2016 - Melnikov, Vitaly; Hüllermeier, Eyke (European Conference on Machine Learning and Knowledge Discovery in Databases, Part II, Riva del Garda, Italy)

Consistency of probalistic classifier trees - Dembczynski, K.; Kotlowski, W.; Waegeman, W.; Busa-Fekete, Robert; Hüllermeier, Eyke (In Proceedings ECML/PKDD European Conference on Maschine Learning and Knowledge Discovery in Databases, Part II, Riva del Garda, Italy)

Predicting the electricity consumption of buildings: An improved CBR approach - Shabani, Aulon; Paul, Adil; Platon, R.; Hüllermeier, Eyke (In Proceedings ICCBR, 24th International Conference on Case-Based Reasoning, Atlanta, GA, USA)

Evaluating tests in medical diagnosis-Combining machine learning with game-theoretical concepts - Pfannschmidt, Karlson; Hüllermeier, Eyke; Held, S.; Neiger, R. (In Proceedings IPMU 16th International Conference on Information Processing and Management of Uncertainty in Knowledge-Based Systems, Part 1, Eindhoven, The Netherlands)

On the Identifiability of models in multi-criteria preference learning - Labreuche, C.; Hüllermeier, Eyke; Vojtas, P.; Fallah Tehrani, A. (Proceedings DA2PL ´2016, Euro Mini Conference from Multiple Criteria Decision Aid to Preference Learning)

Preference-Based Reinforcement Learning Using Dyad Ranking - Schäfer, Dirk; Hüllermeier, Eyke (Proceedings DA2PL ´2016, Euro Mini Conference from Multiple Criteria Decision Aid to Preference Learning)

Statistical Inference for Incomplete Ranking Data: A Comparison of two likelihood-based estimators - Couso, Ines; Ahmadi Fahandar, Mohsen; Hüllermeier, Eyke (Proceedings DA2PL ´2016, Euro Mini Conference from Multiple Criteria Decision Aid to Preference Learning)

Support vector classification on noisy data using fuzzy supersets losses - Lu, S.; Hüllermeier, Eyke (Proceedings 26. Workshop Computational Intelligence, KIT Scientific Publishing)

Plackett-Luce networks for dyad ranking - Schäfer, Dirk; Hüllermeier, Eyke (In Workshop LWDA "Lernen, Wissen, Daten, Analysen")

ECAI 2016, 22nd European Conference on Artificial Intelligence, including PAIS 2016, Prestigious Applications of Artificial Intelligence

CavSimBase: A database for large scale comparison of protein binding sites - Leinweber, M.; Fober, T.; Strickert, M.; Baumgärtner, L.; Klebe, G.; Freisleben, B.; Hüllermeier, Eyke (IEEE Transactions on Knowledge and Data Engineering)

Exploiting HIV-1 protease and reverse transcriptase cross-resistance information for improved drug resistance prediction by means of multi-label classification - Riemenschneider, M.; Senge, Robin; Neumann, U.; Hüllermeier, Eyke; Heider, D. (BioData Mining)

Delayed (de-)activation in servers with a sleep mode - Herlich, Matthias; Bredenbals, Nico; Karl, Holger (Sustainable Computing: Informatics and Systems)

Fast Dynamic Fault Injection for Virtual Microcontroller Platforms - Adelt, Peer; Koppelmann, Bastian; Müller, Wolfgang; Becker, Markus; Kleinjohann, Bernd; Scheytt, Christoph (Proceedings of the IEEE/IFIP International Conference on VLSI (VLSI-SOC))
Electronic systems, like they are embedded in road vehicles, have to be compliant to functional safety standards like ISO 26262 [1], which limit the impacts of malfunctions for safety critical systems. ISO 26262, for instance, defines different safety levels for road vehicles, which require different means and measures for a safety compliant system and its development process like risk analysis and fault effect simulation. For fault effect simulation it is important to investigate the impact of physical and hardware related effects to the correct function of a system. This article first studies code and model mutations for fault injection in the context of fault effect simulation through different system abstraction levels. It demonstrates how high level mutations correlate to bit flips of software binaries by examples from the TriCore™ instruction set and finally presents a virtual platform based implementation for automated injection of bit flip based mutations into software binaries. Experimental results demonstrate the efficiency of the implemented approach.

An all-transmission-line 220 GHz differential LNA in SiGe BiCMOS - Mao, Yanfei; Schmalz, Klaus; Scheytt, Christoph; Shiju, E. (IEEE International Symposium on Radio-Frequency Integration Technology)
This paper presents a four stage all-transmission-line 220 GHz differential LNA in SiGe BiCMOS technology. Cascode topology is chosen for each stage. The amplifier takes advantage of microstrip transmission lines to realize the inductive load, Marshand balun, input, output, and inter-stage matching of the LNA. The LNA has a gain of 21 dB at 224 GHz, a 3 dB bandwidth of more than 6 GHz. It has a supply voltage of 3V and power dissipation of 234 mW. The amplifier is intended for the use in communication, security scanning, imaging and remote sensing at 220 GHz.

Fault Injection and Mixed-Level Simulation for Analog Circuits - A Case Study - Abughannam, Saed; Wu, Liang; Müller, Wolfgang; Scheytt, Christoph; Ecker, Wolfgang; Novello, Christiano (Analog 2016 - VDE)
The design of safety critical systems requires an efficient methodology for an effective fault effect simulation for analog and digital circuits where analog fault injection and fault effect simulation is currently a field of active research and commercial tools are not available yet. This article begins by discussing fault injection strategies for analog circuits applied on a case study with two topologies of a Voltage Controlled Oscillator (VCO). In the second part it performs on the basis of the example of a Wireless Sensor Network (WSN) node, how far different mixed level implementations with Verilog-A and SPICE can affect the simulation time and points out which component consumes the major part of the simulation time.

Obstacle detection using a miniaturized radar sensor operating at 120GHz ISM band - Nava, Federico; Genschow, Dieter; Scheytt, Christoph (DRONE Berlin 2016)
Currently, all drone manufactures face the same problem: flight safety utility will become mandatory to obtain the legal admission for broad commercial use of drones. This means that on-board obstacle detection and collision avoidance is a must-have in order to overcome existing legal barriers and acceptance issues. Some of the currently available sensors are too large, too heavy, or can be poorly integrated into existing systems. During the exhibition a demonstration of a novel micro-sensor operating at 120 GHz will be given and participants will have the chance to experience the device first-hand.

Linear ultra-broadband NPN-only analog correlator at 33 Gbps in 130nm SiGe BiCMOS technology - Javed, Abdul Rehman; Scheytt, Christoph; Von der Ahe, Uwe (IEEE Bipolar/BiCMOS Circuits and Technology Meeting)
An ultra-broadband analog correlator consisting of a four-quadrant multiplier and an ultra-fast resettable integrator using only NPN transistors was designed, fabricated, and measured. For the integrator, a cross-coupled transistor pair is used as a negative resistance generator. A novel ultra-fast reset circuit is implemented which allows to reset the integrator within very short time of 120 ps. The chip was fabricated using 130 nm SiGe BiCMOS technology with fT of 250 GHz and f max of 300 GHz. In the measurements carried out on printed circuit board, the correlator operated without noticeable performance degradation with inputs up to 33 Gbps which correspond to a bandwidth of more than 24 GHz. The correlator exhibits high linearity with output P1dB of more than 9.9 dBm (700 mV diff ) for both inputs. It dissipates 122.5 mW for the core circuit excluding the 50 Ω output driver. To the knowledge of the authors, the circuit represents the fastest analog correlator published so far. It can be used for spread spectrum communication, radar signal processing, and measurement applications.

Hierarchical Scheduling for Plug-and-Produce - Jatzkowski, Jan; Adelt, Peer; Rettberg, Achim (3rd International Conference on System-integrated Intelligence: New Challenges for Product and Production Engineering)
Today's increasing number of sensors and computation nodes covered by cyber physical systems (CPS) results in rising complexity. For instance, computation results are based on measured data whose quality strongly depends on their age. CPS therefore have real-time requirements on computation results and communication to keep temporal dependency between measured inputs and computed outputs. In addition, today's CPS shall be modular to enable flexibility and scalability, e.g., postulated for production systems in context of Industry 4.0. Enabling CPS to easily integrate components by some Plug-and-Produce mechanism is desired.In this paper, we aim at enabling Plug-and-Produce in CPS using hypervisor-based virtualization. This implies hierarchical scheduling of dependent real-time systems. Here, dependencies are given by precedence constraints of tasks. Based on an approach for detection of new components added to a real-time network, in this paper we focus on integration of enabled applications into the current schedule of a computation node. Here, enabled application refers to an application software that just got executable by plugging some component to the CPS. Applications are encapsulated by virtual machines and provide a self-description including information about required and provided data as well as timing behavior. This self-description is used to adjust global scheduling and thus include new functionality to the CPS.

Ultra-compact 122GHz Radar Sensor for Autonomous Aircrafts - Nava, Federico; Scheytt, Christoph; Zwick, Thomas; Pauli, Mario; Goettel, B.; Winkler, Wolfgang (3rd International Conference on System-Integrated Intelligence)
In this paper a prototype of an ultra-compact continuous-wave (CW) and frequency-modulated continuous-wave (FMCW) radar system using a highly-integrated radar chip and in-package antennas will be presented. An introduction will be given on the concept of antenna integration for millimeter-wave radar and the advantages of such systems. The radar then will be described in its main components, a 122 GHz Integrated Circuit including in-package antennas as well as the acquisition and processing system realized using flexible printed circuit board (FLEX PCB) technology. Furthermore initial measurements of the radar system will be presented and explained.

Some reflections on electromagnetic force in matter - Böcker, Joachim (2016 International Symposium on Power Electronics, Electrical Drives, Automation and Motion (SPEEDAM))

Local demand response and load planning system for intelligent domestic appliances - Stille, Karl Stephan Christian; Böcker, Joachim (2015 International Conference on Renewable Energy Research and Applications (ICRERA))

Integration of home photovoltaic generation into electricity tariff for load optimization - Stille, Karl Stephan Christian; Böcker, Joachim; Fröhleke, Norbert; Bettentrup, Ralf; Kaiser, Ingo (2016 4th International Istanbul Smart Grid Congress and Fair (ICSG))

Local grid load coordination for load-shiftable domestic appliances in a variable-tariff environment - Stille, Karl Stephan Christian; Böcker, Joachim; Fröhleke, Norbert; Bettentrup, Ralf; Kaiser, Ingo (2016 18th European Conference on Power Electronics and Applications (EPE'16 ECCE Europe))

Supervisional load optimization for households with intelligent domestic appliances - Stille, Karl Stephan Christian; Böcker, Joachim; Fröhleke, Norbert; Bettentrup, Ralf; Kaiser, Ingo (2016 10th International Conference on Compatibility, Power Electronics and Power Engineering (CPE-POWERENG))

A Critical Review of Techniques to Determine the Magnet Temperature of Permanent Magnet Synchronous Motors under Real-time Conditions - Wallscheid, Oliver; Huber, Tobias; Peters, Wilhelm; Böcker, Joachim (EPE Journal)

Real-time capable model predictive control of permanent magnet synchronous motors using particle swarm optimisation - Wallscheid, Oliver; Ammann, Ulrich; Böcker, Joachim (PCIM Europe 2016; International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management)

2D analytical model for estimation of eddy current loss in the magnets of IPM machines considering the reaction field of the induced eddy currents - Paradkar, Milind; Böcker, Joachim (2015 IEEE International Electric Machines & Drives Conference (IEMDC))

Voltage controller for flux weakening operation of interior permanent magnet synchronous motor in automotive traction applications - Huber, Tobias; Peters, Wilhelm; Böcker, Joachim (2015 IEEE International Electric Machines & Drives Conference (IEMDC))

Analysis of eddy current losses in the stator windings of IPM machines in electric and hybrid electric vehicle applications - Paradkar, M.; Böcker, Joachim (8th IET International Conference on Power Electronics, Machines and Drives (PEMD 2016))

Comparison of quarter-wave with half-wave symmetrical pulse patterns applied in electrical high-speed drives - Peter, K.; Böcker, Joachim; Mink, F.; Beineke, S. (8th IET International Conference on Power Electronics, Machines and Drives (PEMD 2016))

Comparison of Optimized Pulse Patterns with Direct Model Predictive Control Using Co-Simulation - Schulte, C.; Peter, K.; Böcker, Joachim; Leuer, M. (8th IET International Conference on Power Electronics, Machines and Drives (PEMD 2016))

Inverter loss management for an electrical high-speed drive system - Peter, Klaus; Hanke, Soren; Mink, Fabian; Böcker, Joachim (2016 18th European Conference on Power Electronics and Applications (EPE'16 ECCE Europe))

Sensitivity analysis on production tolerances for electric drive systems in automotive application - Ott, Markus; Böcker, Joachim (2016 18th European Conference on Power Electronics and Applications (EPE'16 ECCE Europe))

Model predictive control strategy for multi-phase thyristor matrix converters — Advantages, problems and solutions - Leuer, Michael; Lönneker, Michael; Böcker, Joachim (2016 18th European Conference on Power Electronics and Applications (EPE'16 ECCE Europe))

Comparison of the performance of gallium nitride (GaN) transistors in a totem-pole power factor controlled (PFC) rectifier - Bolte, Sven; Fröhleke, Norbert; Böcker, Joachim (2016 IEEE International Telecommunications Energy Conference (INTELEC))

Determination of storage loss characteristics with reasonable measurement and calculation effort - Vogt, Thorsten; Pahl, Richard; Fröhleke, Norbert; Böcker, Joachim (2016 18th European Conference on Power Electronics and Applications (EPE'16 ECCE Europe))

Direct Model Predictive Control strategy for multi-phase thyristor matrix converters - Leuer, Michael; Lönneker, Michael; Böcker, Joachim (2015 IEEE International Symposium on Predictive Control of Electrical Drives and Power Electronics (PRECEDE))

DC-DC converter design for power distribution systems in electric vehicles using calorimetric loss measurements - Bolte, Sven; Fröhleke, Norbert; Böcker, Joachim (2016 18th European Conference on Power Electronics and Applications (EPE'16 ECCE Europe))

Numerical optimization of passive line filter components for suppression of electromagnetic interference (EMI) - Henkenius, Carsten; Fröhleke, Norbert; Böcker, Joachim; Figge, Heiko (2016 IEEE Applied Power Electronics Conference and Exposition (APEC))

Efficiency optimization for a power factor correction (PFC) rectifier with gallium nitride transistor - Bolte, Sven; Fröhleke, Norbert; Böcker, Joachim (2015 IEEE 3rd Workshop on Wide Bandgap Power Devices and Applications (WiPDA))

Analysis and design of integrated common and differential mode inductors - Henkenius, Carsten; Fröhleke, Norbert; Böcker, Joachim (2016 IEEE International Telecommunications Energy Conference (INTELEC))

Experimentelle Identifikation eines thermischen Modells zur Überwachung kritischer Temperaturen in hochausgenutzten permanenterregten Synchronmotoren für automobile Traktionsanwendungen - Huber, Tobias

High Power LLC Resonant Converter Optimized for High Efficiency and Industrial Use - Figge, H.

Compact Storage Based Resistance Spot Welding Power Supplies - Dora Venkata Mohana Murali, K,

»Mathematik inklusive«: Lernchancen im inklusiven Anfangsunterricht. - Häsel-Weide, Uta (Beiträge zum Mathematikunterricht. Vorträge auf der 50. Tagung für Didaktik der Mathematik)

Mathematik gemeinsam lernen - Lernumgebungen für den inklusiven Mathematikunterricht. - Häsel-Weide, Uta (Tagungsband des AK Grundschule in der GDM 2016)

"Merit hat 4 von 5 Subtraktionsaufgaben durch Rückwärtszählen gelöst". Leistungsbeurteilung im inklusiven Mathematikunterricht - Häsel-Weide, Uta (Sonderpädagogische Förderung heute)

Vom Zählen zum Rechnen. Struktur-fokussierende Deutungen in kooperativen Lernumgebungen. - Häsel-Weide, Uta

Gemeinsam ordnen – gemeinsam lernen. Mathematische Strukturen sichtbar machen. - Häsel-Weide, Uta (Grundschulunterricht Mathematik)

On the weakly competitive case in a two-species chemotaxis model - Black, Tobias; Lankeit, Johannes; Mizukami, Masaaki (IMA Journal of Applied Mathematics)
Keywords: Applied Mathematics

Boundedness in a Keller–Segel system with external signal production - Black, Tobias (Journal of Mathematical Analysis and Applications)
Keywords: Applied Mathematics; Analysis

Blow-up of weak solutions to a chemotaxis system under influence of an external chemoattractant - Black, Tobias (Nonlinearity)
Keywords: Applied Mathematics; General Physics and Astronomy; Mathematical Physics; Statistical and Nonlinear Physics

Sublinear signal production in a two-dimensional Keller–Segel–Stokes system - Black, Tobias (Nonlinear Analysis: Real World Applications)
Keywords: Applied Mathematics; Computational Mathematics; General Economics; Econometrics and Finance; General Engineering; General Medicine; Analysis

A comparison of two predictive approaches to control the longitudinal dynamics of electric vehicles - Eckstein, Julian; Peitz, Sebastian; Schäfer, Kai; Friedel, Patrick; Köhler, Ulrich; Hessel von Molo, Mirko; Ober-Blöbaum, Sina; Dellnitz, Michael (Procedia Technology, 3rd International Conference on System-Integrated Intelligence: New Challenges for Product and Production Engineering)
In this contribution we compare two different approaches to the implementation of a Model Predictive Controller in an electric vehicle with respect to the quality of the solution and real-time applicability. The goal is to develop an intelligent cruise control in order to extend the vehicle range, i.e. to minimize energy consumption, by computing the optimal torque profile for a given track. On the one hand, a path-based linear model with strong simplifications regarding the vehicle dynamics is used. On the other hand, a nonlinear model is employed in which the dynamics of the mechanical and electrical subsystem are modeled.

Variational integrators of mixed order for dynamical systems with multiple time scales and split potentials - Wenger, T.; Ober-Blöbaum, Sina; Leyendecker, S. (ECCOMAS Congress 2016 - Proceedings of the 7th European Congress on Computational Methods in Applied Sciences and Engineering)

Constrained Galerkin variational integrators and modified constrained symplectic Runge-Kutta methods - Wenger, T.; Ober-Blöbaum, Sina; Leyendecker, S. (International Conference of Numerical Analysis and Applied Mathematics (ICNAAM))

Reduced order model based multiobjective optimal control of fluids - Peitz, Sebastian; Ober-Blöbaum, Sina; Dellnitz, M. (Proceedings of International Congress of Theoretical and Applied Mechanics)

Optimal control of switching times in switched linear systems - Stellato, B.; Ober-Blöbaum, Sina; Goulart, P.J. (2016 IEEE 55th Conference on Decision and Control (CDC))

Symmetry reduction of holomorphic iterated function schemes and factorization of Selberg zeta functions - Borthwick, David; Weich, Tobias (Journal of Spectral Theory)
Keywords: Geometry and Topology; Mathematical Physics; Statistical and Nonlinear Physics

On the Support of Pollicott–Ruelle Resonanant States for Anosov Flows - Weich, Tobias (Annales Henri Poincaré)
Keywords: Mathematical Physics; Nuclear and High Energy Physics; Statistical and Nonlinear Physics

Spectral analysis of the diffusion operator with random jumps from the boundary - Kolb, Martin; Krejčiřík, David (Mathematische Zeitschrift)
Using an operator-theoretic framework in a Hilbert-space setting, we perform a detailed spectral analysis of the one-dimensional Laplacian in a bounded interval, subject to specific non-self-adjoint connected boundary conditions modelling a random jump from the boundary to a point inside the interval. In accordance with previous works, we find that all the eigenvalues are real. As the new results, we derive and analyse the adjoint operator, determine the geometric and algebraic multiplicities of the eigenvalues, write down formulae for the eigenfunctions together with the generalised eigenfunctions and study their basis properties. It turns out that the latter heavily depend on whether the distance of the interior point to the centre of the interval divided by the length of the interval is rational or irrational. Finally, we find a closed formula for the metric operator that provides a similarity transform of the problem to a self-adjoint operator.

Lower Bound on the Mean Square Displacement of Particles in the Hard Disk Model - Richthammer, Thomas (Communications in Mathematical Physics)
The hard disk model is a 2D Gibbsian process of particles interacting via pure hard core repulsion. At high particle density the model is believed to show orientational order, however, it is known not to exhibit positional order. Here we investigate to what extent particle positions may fluctuate. We consider a finite volume version of the model in a box of dimensions 2n × 2n with arbitrary boundary configuration, and we show that the mean square displacement of particles near the center of the box is bounded from below by c log n. The result generalizes to a large class of models with fairly arbitrary interaction.

Transience and recurrence of a Brownian path with limited local time - Kolb, Martin; Savov, Mladen (The Annals of Probability)
In this note we investigate the behaviour of Brownian motion conditioned on a growth constraint of its local time which has been previously investigated by Berestycki and Benjamini. For a class of non-decreasing positive functions f(t);t>0, we consider the Wiener measure under the condition that the Brownian local time is dominated by the function f up to time T. In the case where f(t)/t3/2 is integrable we describe the limiting process as T goes to infinity. Moreover, we prove two conjectures in [BB10] in the case for a class of functions f, for which f(t)/t3/2 just fails to be integrable. Our methodology is more general as it relies on the study of the asymptotic of the probability of subordinators to stay above a given curve. Immediately or with adaptations one can study questions like the Brownian motioned conditioned on a growth constraint of its local time at the maximum or more generally a Levy process conditioned on a growth constraint of its local time at the maximum or at zero. We discuss briefly the former.

Vandalism Detection in Wikidata - Heindorf, Stefan; Potthast, Matthias; Stein, Benno; Engels, Gregor (Proceedings of the 25th International Conference on Information and Knowledge Management (CIKM 2016))
Wikidata is the new, large-scale knowledge base of the Wikimedia Foundation. Its knowledge is increasingly used within Wikipedia itself and various other kinds of information systems, imposing high demands on its integrity.Wikidata can be edited by anyone and, unfortunately, it frequently gets vandalized, exposing all information systems using it to the risk of spreading vandalized and falsified information. In this paper, we present a new machine learning-based approach to detect vandalism in Wikidata.We propose a set of 47 features that exploit both content and context information, and we report on 4 classifiers of increasing effectiveness tailored to this learning task. Our approach is evaluated on the recently published Wikidata Vandalism Corpus WDVC-2015 and it achieves an area under curve value of the receiver operating characteristic, ROC-AUC, of 0.991. It significantly outperforms the state of the art represented by the rule-based Wikidata Abuse Filter (0.865 ROC-AUC) and a prototypical vandalism detector recently introduced by Wikimedia within the Objective Revision Evaluation Service (0.859 ROC-AUC).

Low-Power, Ultra-compact, Fully-differential 40Gbps Direct Detection Receiver in 0.25μm Photonic BiCMOS SiGe Technology - Gudyriev, Sergiy; Scheytt, Christoph; Meister, Stefan; Knoll, Dieter; Lischke, Stefan; Zimmermann, Lars; Meuer, Christian (IEEE Group IV Photonics Conference)
Recently electronic-photonic integrated circuits (EPIC) technology platforms became available [1] which allow fabrication of very compact and fast monolithic receivers. However, although the cointegration of electronics and photonics on the same chip allows for novel circuit topologies which could help to improve circuit performance quite often transmitter and receiver circuit design is using more or less conventional approaches. We propose a novel architecture that effectively utilizes the benefits of the EPIC technology such as: very short interconnects between the photodiode and the amplifier, symmetrical and compact photodiode structure with low operating voltages. Our architecture shown in Fig. 1 features fully-differential input stage, automatic biasing of the photodiode, DC coupling between diode and transimpedance amplifier (TIA) and very small footprint.

Recent Advances in Millimeter-Wave-and Electronic-Photonic System-on-Chip Design - Scheytt, Christoph (Microelectronics Seminar)

Adaptive Seeding for Gaussian Mixture Models - Blömer, Johannes; Bujna, Kathrin (Advances in Knowledge Discovery and Data Mining)

Projekt WiGeMath: Wirkung und Gelingensbedingungen von Unterstützungsmaßnahmen für mathematikbezogenes Lernen in der Studieneingangsphase - Colberg, Christoph; Schürmann, Mirko; Biehler, Rolf; Hochmuth, Reinhard Karl; Schaper, Niclas; Liebendörfer, Michael (Working Paper Studieneingangsphase Perspektiven aus der Begleitforschung zum Qualitätspakt Lehre)

Wirkung und Gelingensbedingungen von Unterstützungsmaßnahmen für mathematikbezogenes Lernen in der Studieneingangsphase - Colberg, Christoph; Biehler, Rolf; Hochmuth, Reinhard; Schaper, Niclas; Liebendörfer, Michael; Schürmann, Mirko (Beiträge zum Mathematikunterricht 2016)

Design of voltage controlled oscillators (VCOs) in D-band and their phase noise measurements using frequency down-conversion - Ali, U.; Bober, M.; Thiede, Andreas (2016 11th European Microwave Integrated Circuits Conference (EuMIC))

Comparison of Cost and Complexity for Various 16-QAM Transmitter Structures in Coherent Optical Systems - Al-Bermani, Ali; Noé, Reinhold (NEXT-GENERATION OPTICAL COMMUNICATION: COMPONENTS, SUB-SYSTEMS, AND SYSTEMS V)

LiNbO3-Based Endless Optical Polarization Control The Photonic Alternative to Coherent Electronics - Noé, Reinhold; Koch, Benjamin; Mirvoda, Vitali (2016 21ST EUROPEAN CONFERENCE ON NETWORKS AND OPTICAL COMMUNICATIONS (NOC))

Time-resolved Mueller matrix measurement and polarization scrambler characterization - Koch, Benjamin; Noé, Reinhold; Mirvoda, Vitali (2016 21st European Conference on Networks and Optical Communications (NOC))

LiNbO3-based endless optical polarization control - Noé, Reinhold; Koch, Benjamin; Mirvoda, Vitali (2016 21st European Conference on Networks and Optical Communications (NOC))

Accelerated Testing of Polarization-Tracking Receiver Using Polarization Scrambler with Peaked Speed Distribution - Koch, Benjamin; Noé, Reinhold; Mirvoda, Vitali; Sandel, David (Photonic Networks; 17. ITG-Symposium; Proceedings of)

Integral representation and sharp asymptotic results for some Heckman-Opdam hypergeometric functions of type BC - Rösler, Margit; Voit, Michael (Transactions of the American Mathematical Society)

A multivariate version of the disk convolution - Rösler, Margit; Voit, Michael (Journal of Mathematical Analysis and Applications)
Keywords: Applied Mathematics; Analysis

Time-Resolved Mueller Matrix Measurement and Polarization Scrambler Characterization - Koch, Benjamin; Noé, Reinhold; Mirvoda, Vitali (2016 21ST EUROPEAN CONFERENCE ON NETWORKS AND OPTICAL COMMUNICATIONS (NOC))

Bayesian Information Criterion for Source Enumeration in Large-Scale Adaptive Antenna Array - Huang, Lei; Xiao, Yu-Hang; Liu, Kefei; So, Hing Cheung; Zhang, Jian-Kang (IEEE Transactions on Vehicular Technology)

Shrinkage of covariance matrices for linear signal estimation using cross-validation - Tong, Jun; Schreier, Peter J.; Guo, Qinghua; Tong, S.; Xi, Jiangtao; Yu, Y. (IEEE Trans.\ Signal\ Process.)

DOA parameter estimation with 1-bit quantization - Bounds, methods and the exponential replacement - Stein, Manuel; Barbé, Kurt; Nossek, Josef A. (Proc.\ ITG Int.\ Work. Smart Ant.)

Asymptotic performance analysis for $1$-bit Bayesian smoothing - Zhang, Lin; Stein, Manuel; Nossek, Josef A. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)

Performance analysis for pilot-based $1$-bit channel estimation with unknown quantization threshold - Stein, Manuel; Bar, Shahar; Nossek, Josef A.; Tabrikian, Joseph (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)

Choosing the diagonal loading factor for linear signal estimation using cross validation - Tong, Jun; Guo, Qinghua; Xi, Jiangtao; Yu, Y.; Schreier, Peter J. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)

Adaptive visual sort and summary of micrographic images of nanoparticles for forensic analysis - Jurrus, Elizabeth; Hodas, Nathan; Baker, Nathan; Marrinan, Tim; Hoover, Mark D (Technologies for Homeland Security (HST), 2016 IEEE Symposium on)

Accurate Asymptotic Analysis for Johns Test in Multichannel Signal Detection - Xiao, Y-.H.; Huang, L.; Xie, J.; H. C. So, and (Proc. IEEE Int. Conf. Acoust., Speech, Signal Process. (ICASSP))

Canonical correlation analysis of high-dimensional data with very small sample support - Song, Yang; Schreier, Peter J.; Ramírez, David; Hasija, Tanuj (Signal Process.)

Detecting the dimension of the subspace correlated across multiple data sets in the sample poor regime - Hasija, Tanuj; Song, Yang; Schreier, Peter J.; Ramírez, David (Proc.\ IEEE Work.\ Stat.\ Signal Process.)

Bootstrap-based detection of the number of signals correlated across multiple data sets - Hasija, Tanuj; Song, Yang; Schreier, Peter J.; Ramírez, David (Proc.\ Asilomar Conf.\ Signals\ Syst. Computers)

Determining the number of signals correlated across multiple data sets for small sample support - Song, Yang; Hasija, Tanuj; Schreier, Peter J.; Ramírez, David (Proc.\ Eur.\ Signal Process.\ Conf.)

Hardy–Stein identities and square functions for semigroups - Bañuelos, Rodrigo; Bogdan, Krzysztof; Luks, Tomasz (Journal of the London Mathematical Society)
Keywords: General Mathematics

Simulations of high harmonic generation from plasmonic nanoparticles in the terahertz region - Grynko, Yevgen; Zentgraf, Thomas; Meier, Torsten; Förstner, Jens (Applied Physics B)
Keywords: tet_topic_meta; tet_topic_shg

Detection of cyclostationarity in the presence of temporal or spatial structure with applications to cognitive radio - Pries, Aaron; Ramírez, David; Schreier, Peter J. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)
One approach to spectrum sensing for cognitive radio is the detection of cyclostationarity. We extend an existing multi-antenna detector for cyclostationarity proposed by Ramírez et al. [1], which makes no assumptions about the noise beyond being (temporally) wide-sense stationary. In special cases, the noise could be uncorrelated among antennas, or it could be temporally white. The performance of a general detector can be improved by making use of a priori structural information. We do not, however, require knowledge of the exact values of the temporal or spatial noise covariances. We develop an asymptotic generalized likelihood ratio test and evaluate the performance by simulations.

Flag-based detection of weak gas signatures in long-wave infrared hyperspectral image sequences. - Marrinan, Tim; Beveridge, J. Ross; Draper, Bruce; Kirby, Michael; Peterson, Chris (SPIE Defense, Security, and Sensing)

A unified scheme to achieve the degrees-of-freedom region of the MIMO interference channel with delayed channel state information - Rezaee, Mohsen; Schreier, Peter J.; Guillaud, M.; Clerckx, B. (IEEE Trans.\ Comm.)